Maori Fisheries 1986-1998: A Reflection - Boast, Richard (Victoria University of Wellington Law Review, 1999)
In this article Richard Boast considers the statutory settlements of Maori fishing claims made in 1989 and 1992. These settlements are seen as examples of a distinctive method of dealing with Maori grievances routinely used in the New Zealand legal and political system. He also considers the aftermath of the legislation, and the extent to which the recent claims of Urban Maori authorities have questioned the entire settlement process as it has evolved to date.